2009
DOI: 10.1016/j.socscimed.2009.05.035
|View full text |Cite
|
Sign up to set email alerts
|

Gender asymmetry in healthcare-facility attendance of people living with HIV/AIDS in Burkina Faso

Abstract: Anthropological research in Burkina Faso indicates that more HIV-positive women than HIV-positive men are attending care facilities for people living with HIV/AIDS (PLWH) and accessing antiretroviral medicine. This article, situated in the field of study of interactions between gender and AIDS, offers a description of this asymmetry and an anthropological analysis of the socio-cultural determinants, through analysis of data from ethnographic research among PLWH and health actors. Examining social representatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
39
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 15 publications
6
39
2
Order By: Relevance
“…Our findings on masculinity-related barriers to the HIV treatment cascade in this particular South African context are consistent with findings from other research in sub-Saharan Africa (Bila and Egrot 2009; Nyamhanga et al 2013; Siu et al 2013; Siu et al 2012; 2014a; Siu et al 2014b). Our results are novel, however, because they show how a gender-transformative intervention influences several key mechanisms that may improve men’s HIV testing and treatment outcomes.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our findings on masculinity-related barriers to the HIV treatment cascade in this particular South African context are consistent with findings from other research in sub-Saharan Africa (Bila and Egrot 2009; Nyamhanga et al 2013; Siu et al 2013; Siu et al 2012; 2014a; Siu et al 2014b). Our results are novel, however, because they show how a gender-transformative intervention influences several key mechanisms that may improve men’s HIV testing and treatment outcomes.…”
Section: Discussionsupporting
confidence: 91%
“…In large multi-site cohort studies of persons living with HIV in South Africa who had initiated ARV treatment, men were significantly more likely than women to be lost to follow-up (Cornell et al 2014), have a lower median CD4+ count, and higher crude and age-adjusted mortality (Cornell et al 2012). Researchers in other settings in sub-Saharan Africa have found similar differences between men and women (Bila and Egrot 2009; Gari et al 2014; Parrott et al 2011). To reduce HIV transmission through HIV testing/care/treatment, it is therefore essential to improve our understanding of the barriers that are unique to men and what programmes can do to ameliorate this gender difference.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…Varied study periods, different follow-up times and different ART eligibility criteria across studies could all contribute to the variability in study estimates. Nevertheless, pooled estimates of current ART use among HIV-infected FSWs are similar to estimates of current ART use among HIV-infected women in Burkina Faso (27%) and among HIV-infected female IDUs in Canada (30%) [62], [63]. Likewise, in the one study in Rwanda that reported ART initiation among ART-eligible FSWs, the proportion of ART-eligible FSWs in HIV care initiating ART was similar to the proportion of ART-eligible individuals in the Rwandan general population initiating ART (71%) [42].…”
Section: Discussionmentioning
confidence: 60%
“…Countless studies on gender and healthseeking behaviours already report the asymmetry between women and men. Regarding HIV and AIDS, solid evidence points to a gender specificity in voluntary counselling and testing (Le Coeur, Collins, Pannetier & Lelièvre 2009;Obermeyer & Osborn 2007), disclosure to partners (Ndiaye, Boileau, Zunzunegui, Koala, Aboubacrine, Niamba, et al 2008;Tijou, Querre, Brou, Leroy, Desclaux, & Desgrées-du-Loû 2009) and in access and use of HAART (Bila & Egrot 2009 The possible transmission of HIV from mother-to-child adds to the complexity of the gender dimension. Indeed, some children may be infected by HIV themselves.…”
Section: Hiv and Gendermentioning
confidence: 99%